2008
DOI: 10.1007/s12215-008-0001-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-special scrolls with general moduli

Abstract: Abstract. In this paper we study smooth, non-special scrolls S of degree d, genus g ≥ 0, with general moduli. In particular, we study the scheme of unisecant curves of a given degree on S. Our approach is mostly based on degeneration techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…In § 2 we collect standard definitions and properties of scrolls and unisecant curves. In § 3 we recall the results in [5] and in [6]. In §'s 4 and 5 we prove the above-mentioned results of the Brill-Noether theory, whereas § 6 contains the enumerative result.…”
Section: Let [S]mentioning
confidence: 92%
See 4 more Smart Citations
“…In § 2 we collect standard definitions and properties of scrolls and unisecant curves. In § 3 we recall the results in [5] and in [6]. In §'s 4 and 5 we prove the above-mentioned results of the Brill-Noether theory, whereas § 6 contains the enumerative result.…”
Section: Let [S]mentioning
confidence: 92%
“…In [6] we showed that, if g ≥ 1 and S is general, then F is general in U C (d) (cf. [2] and [6,Theorem 5.5]). We then proved that S is a general ruled surface in the sense of Ghione [12], namely the scheme Div 1,m S parametrizing unisecant curves of given degree m on S behaves as expected (for details, cf.…”
Section: Let [S]mentioning
confidence: 99%
See 3 more Smart Citations